Unified Sequent Calculi and Natural Deduction Systems for Until-free Linear-time Temporal Logics - Kamide, Norihiro; Negri, Sara (Bulletin of the Section of Logic, 2025)
A unified Gentzen-style proof-theoretic framework for until-free propositional linear-time temporal logic and its intuitionistic variant is introduced. The framework unifies Gentzen-style single-succedent sequent calculi and natural deduction systems for both the classical and intuitionistic versions of these temporal logics. Theorems establishing the equivalence between the proposed sequent calculi and natural deduction systems are proved. Furthermore, the cut-elimination theorems for the proposed sequent calculi and the normalization theorems for the proposed natural deduction systems are established.